Manganese-based positive electrode material of zinc ion battery as well as preparation method and application of manganese-based positive electrode material
By adding metaborate-based compounds to the manganese-based oxides to form a composite positive electrode material and treating the surface using the solution method, the problems of unstable structure of the manganese-based positive electrode material and excessive deposition of by-products are solved, and the capacity and cycle stability of the zinc ion battery are improved.
Patent Information
- Application Number
- CN202411699714.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-11-26
AI Technical Summary
The manganese-based positive electrode material of zinc ion battery has problems such as structural instability, capacity attenuation and over-deposition of by-products, resulting in rapid capacity attenuation and poor cycle stability of the battery in practical applications.
By adding metaborate compound to the manganese-based oxide, a composite positive electrode material of manganese-based compound and metaborate compound is formed. The surface of the manganese-based positive electrode material is treated by a simple solution method to form a reversible boron-containing protective layer to inhibit excessive deposition of by-products and manganese dissolution.
It improves the structural stability and electrochemical performance of manganese-based positive electrode materials, enhances the capacity and rate performance of zinc ion batteries, and extends the cycle life of the battery.
Smart Images

Figure CN119725430A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of zinc ion battery materials, and in particular to a manganese-based positive electrode material for a zinc ion battery, and a preparation method and application thereof. Background Art
[0002] In view of the continuous depletion of traditional fossil energy and the growing demand for flexible and wearable portable batteries in modern people, it is urgent to discover cleaner and more environmentally friendly energy storage devices. Although lithium-ion batteries (LIBs) have been widely used in the market, they still have problems such as limited capacity, high cost, high risk factor and insufficient cleanliness, which hinder their further development.
[0003] Zinc-ion battery energy storage system has excellent theoretical capacity (819mAh g -1 ), high energy density (5851mAhcm -3 ), suitable redox potential and abundant natural resources, mild aqueous electrolytes and other advantages, which promote commercial production by avoiding harsh manufacturing procedures, thereby significantly reducing costs. With the demand for portable and bendable devices, coupled with the continuous deepening of gel electrolyte research, flexible aqueous zinc-manganese-based batteries have gradually become a development trend. In short, aqueous zinc-ion batteries, as a new type of environmentally friendly energy storage element, have research potential to be explored.
[0004] At present, the structural instability and excessive formation of by-products of manganese-based cathode materials for zinc-ion batteries have become the decisive factors restricting the development of zinc-ion batteries. Therefore, the development of more stable new cathode materials and the inhibition of the formation of side reaction products are the key to the development of zinc-ion batteries. Layered manganese dioxide has the advantages of environmental protection, economy, high working voltage and large theoretical capacity, and is a promising cathode material for aqueous zinc batteries. However, it faces challenges such as narrow interlayer spacing, poor structural stability, low conductivity and excessive deposition of discharge by-product Zn4SO4(OH)6·5H2O on the cathode surface. These problems lead to rapid capacity decay and poor cycle stability of the battery in practical applications, which seriously hinders the application of manganese-based cathode materials in high-performance aqueous zinc-ion batteries. Therefore, choosing a suitable method to adjust the structure of manganese-based cathode materials to improve their electrochemical performance is a very practical research direction.
[0005] Regarding the problems of capacity attenuation, structural instability and excessive deposition of by-products in manganese-based positive electrode materials, according to a large number of previous experimental studies and theoretical analysis, the above problems are mainly caused by the structural instability, excessive manganese dissolution and excessive deposition of by-products of manganese-based positive electrode materials during the charging and discharging process. Structural instability makes the manganese-based positive electrode material reversible, and the original structure collapses during the charging and discharging process, making it impossible for zinc ions and hydrogen ions to be transmitted normally. Excessive manganese dissolution reduces the reactive substances and seriously hinders the battery capacity. Excessive deposition of by-products also hinders the effective transmission of various active substances in the electrolyte and the reversibility of the battery. Therefore, during the charging and discharging process, the overall structural degradation of the material seriously affects the performance stability of the electrode material. However, there is currently no simple and effective treatment method to improve the above defects. Summary of the invention
[0006] In response to the problems and needs raised above, this proposal proposes a manganese-based positive electrode material for zinc-ion batteries, a preparation method and application thereof. By adopting the following technical features, the above technical objectives can be achieved and many other technical effects can be brought about.
[0007] One object of the present invention is to propose that the positive electrode material is a composite material formed by adding a metaborate-based compound to a manganese-based oxide, wherein the metaborate-based compound includes at least one of seven types: lithium metaborate, sodium metaborate, potassium metaborate, iron metaborate, magnesium metaborate, manganese metaborate, and aluminum metaborate; and the manganese-based oxide includes at least one of nine types: α-MnO2, β-MnO2, γ-MnO2, δ-MnO2, T-MnO2, λ-MnO2, Mn2O3, Mn3O4, and ZnMn2O4.
[0008] In addition, the manganese-based positive electrode material for zinc ion batteries according to the present invention may also have the following technical features:
[0009] Another object of the present invention is to provide a method for preparing the manganese-based positive electrode material for zinc ion batteries as described above, comprising the following steps:
[0010] S10: Put the strong oxidant and manganese salt into a beaker under mechanical stirring, add deionized water and stir evenly;
[0011] S20: transferring the above solution into a high pressure reactor with a polytetrafluoroethylene liner, and then heating it in an oven;
[0012] S30: After cooling, precipitation, filtration, washing, and multiple times, the precursor of the manganese-based positive electrode material is obtained by vacuum drying in an oven;
[0013] S40: Put a metaboric acid compound into a beaker, add deionized water and stir, immerse the manganese-based positive electrode material precursor in the solution, and stir at room temperature;
[0014] S50: The beaker is moved into an oven for drying and evaporation to obtain a manganese-based positive electrode material. During the process, a manganese-based compound and a metaboric acid-based compound composite positive electrode material is formed.
[0015] In one example of the present invention, in step S10, the strong oxidant is permanganate, persulfate or peroxide.
[0016] In one example of the present invention, the strong oxidant is AMnO4, wherein A is at least one of six metal ions of Li, Na, K, Ca, Mg, and Zn; the persulfate is MS2O8, wherein M is at least one of three substances of NH4, Na, and K; and the peroxide is at least one of two substances of K2O2 and H2O2.
[0017] In one example of the present invention, in step S10, the manganese salt is at least one of manganese sulfate, manganese acetate, manganese chloride, and manganese carbonate.
[0018] In one example of the present invention, in the step S30, after cooling, precipitation, filtration, washing for multiple times, the precursor is placed in an oven at 80-110° C. and vacuum dried to obtain a manganese-based positive electrode material precursor.
[0019] In one example of the present invention, in step S40, the metaboric acid-based compound is RBO2, wherein R is at least one of seven substances: Li, Na, K, Fe, Mg, Mn, and Al.
[0020] In one example of the present invention, in step S40, the mass ratio of the manganese-based oxide to the metaboric acid-based compound is 1:0.01-0.5.
[0021] In one example of the present invention, in step S40, the beaker is moved into an oven at 60-80°C for drying and evaporation to obtain a manganese-based positive electrode material, and a manganese-based compound and a metaboric acid-based compound composite positive electrode material are formed in the process.
[0022] Another object of the present invention is to propose an application of the method for preparing a manganese-based positive electrode material for a zinc ion battery as described above to prepare a positive electrode material, characterized in that the positive electrode material prepared by the preparation method is applied to a positive electrode material of a zinc ion battery or a power battery.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] 1. The present invention adopts a simple solution method to treat the surface of the manganese-based positive electrode material, thereby forming a manganese-based compound and a metaboric acid-based compound composite positive electrode material. The method is easy to operate, simple and convenient, and the metaboric acid-based compound is low in price and rich in content, suitable for large-scale production and commercial application, and has extremely significant practical application significance.
[0025] 2. The modification treatment of adding metaboric acid-based compounds of the present invention also affects the reaction process of charging and discharging of manganese-based positive electrode materials. In experimental applications, it is found that it reversibly forms a boron-containing protective layer (including MnBx, zinc boride, etc., x is 1 / 2, 1, 2, etc.) on the surface of manganese-based positive electrode materials. These compounds accelerate the ion diffusion rate by suppressing the excessive deposition of reaction byproducts, suppressing manganese dissolution, and strengthening the structural stability of manganese-based positive electrode materials, thereby improving the capacity and rate performance of zinc ion batteries. In combination with the above advantages, it can be concluded that the manganese-based positive electrode materials for zinc ion batteries that add metaboric acid-based compounds have a very broad application prospect, and developing them as zinc ion battery positive electrode materials is of great practical significance.
[0026] The best embodiment for carrying out the present invention will be described in more detail below with reference to the accompanying drawings so that the features and advantages of the present invention can be easily understood. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings of the embodiments of the present invention, wherein the drawings are only used to illustrate some embodiments of the present invention, but not to limit all embodiments of the present invention thereto.
[0028] Figure 1 Transmission electron microscope images of the δ-MnO2 positive electrode material before and after treatment according to Example 1 of the present invention;
[0029] Figure 2 The X-ray diffraction pattern of the δ-MnO2 positive electrode material powder before and after treatment in Example 1;
[0030] Figure 3 The XPS graphs of the δ-MnO2 cathode material before and after treatment in Example 1;
[0031] Figure 4 The XRD diagram of the δ-MnO2 positive electrode material in Example 1 during the charge and discharge process after treatment;
[0032] Figure 5 This is a cycle performance curve diagram of the δ-MnO2 positive electrode material powder before and after treatment in Example 1 as a positive electrode at room temperature when the current density is 500, 1000, 2000 and 4000 mA / g respectively. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical solution and advantages of the technical solution of the present invention clearer, the technical solution of the embodiment of the present invention will be clearly and completely described in conjunction with the drawings of specific embodiments of the present invention. The same figure marks in the drawings represent the same parts. It should be noted that the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the described embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] Unless otherwise defined, the technical terms or scientific terms used herein shall have the usual meanings understood by persons of ordinary skill in the field to which the present invention belongs. The words "first", "second" and similar words used in the patent application specification and claims of the present invention do not indicate any order, quantity or importance, but are only used to distinguish different components. Similarly, words such as "one" or "one" do not necessarily indicate a quantity limitation. Words such as "include" or "comprise" mean that the elements or objects appearing before the word include the elements or objects listed after the word and their equivalents, without excluding other elements or objects. Words such as "connect" or "connected" are not limited to physical or mechanical connections, but may include electrical connections, whether direct or indirect. "Up", "down", "left", "right" and the like are only used to indicate relative positional relationships. When the absolute position of the described object changes, the relative positional relationship may also change accordingly.
[0035] According to the first aspect of the present invention, the positive electrode material is a composite material formed by adding a metaborate-based compound to a manganese-based oxide, wherein the metaborate-based compound includes at least one of lithium metaborate, sodium metaborate, potassium metaborate, iron metaborate, magnesium metaborate, manganese metaborate, and aluminum metaborate; and the manganese-based oxide includes at least one of α-MnO2, β-MnO2, γ-MnO2, δ-MnO2, T-MnO2, λ-MnO2, Mn2O3, Mn3O4, and ZnMn2O4.
[0036] The cathode material of the present invention uses a simple solution method to treat the surface of the manganese-based cathode material, thereby forming a composite cathode material of a manganese-based compound and a metaboric acid-based compound. The method is easy to operate, simple and convenient, and the metaboric acid-based compound is low in price and rich in content, suitable for large-scale production and commercial application, and has extremely significant practical application significance.
[0037] The modification treatment of adding metaboric acid-based compounds of the present invention also affects the reaction process of charging and discharging of manganese-based positive electrode materials. In experimental applications, it is found that a boron-containing protective layer (including MnBx, zinc boride, etc., x is 1 / 2, 1, 2, etc.) is reversibly formed on the surface of manganese-based positive electrode materials. These compounds accelerate the ion diffusion rate by suppressing the excessive deposition of reaction byproducts, suppressing manganese dissolution, and strengthening the structural stability of manganese-based positive electrode materials, thereby improving the capacity and rate performance of zinc ion batteries. Combined with the above advantages, it can be concluded that the manganese-based positive electrode material of zinc ion batteries adding metaboric acid-based compounds has a very broad application prospect, and developing it as a positive electrode material for zinc ion batteries is of great practical significance.
[0038] According to the second aspect of the present invention, a method for preparing the manganese-based positive electrode material for a zinc ion battery as described above comprises the following steps:
[0039] S10: Put the strong oxidant and manganese salt into a beaker under mechanical stirring, add deionized water and stir evenly;
[0040] S20: transferring the above solution into a high pressure reactor with a polytetrafluoroethylene liner, and then heating it in an oven;
[0041] S30: After cooling, precipitation, filtration, washing, and multiple times, the precursor of the manganese-based positive electrode material is obtained by vacuum drying in an oven;
[0042] S40: Put a metaboric acid compound into a beaker, add deionized water and stir, immerse the manganese-based positive electrode material precursor in the solution, and stir at room temperature;
[0043] S50: The beaker is moved into an oven for drying and evaporation to obtain a manganese-based positive electrode material. During the process, a manganese-based compound and a metaboric acid-based compound composite positive electrode material are formed.
[0044] Specifically, S10: put a strong oxidant and a manganese salt into a beaker under mechanical stirring, add 50-80 mL of deionized water and stir for 0.5-1 h; S20: move the above solution into a high-pressure reactor with a polytetrafluoroethylene liner, and then put it into an oven preheated to 120-200°C and heat it for 8-24 h; S30: after cooling, precipitation, filtration, washing for multiple times, put it into an oven at 80-110°C and vacuum dry it to obtain a manganese-based positive electrode material precursor; S40: take a metaborate compound and put it into a beaker, add 50-100 mL of deionized water and stir for 0.5-1 h, then immerse the manganese-based positive electrode material precursor in the above solution, and stir at room temperature for 0.5-1 h; S50: move the beaker into an oven at 60-80°C to dry and evaporate to obtain a manganese-based positive electrode material, and a manganese-based compound and a metaborate compound composite positive electrode material are formed in the process.
[0045] For example, S10: put a strong oxidant and a manganese salt into a beaker under mechanical stirring, add 60 mL of deionized water and stir for 1 hour; S20: transfer the above solution into a high-pressure reactor (100 mL) with a polytetrafluoroethylene liner, and then put it into an oven preheated to 160°C and heated for 12 hours; S30: after cooling, precipitation, filtration, washing, and vacuum drying in an oven at 110°C for multiple times, a manganese-based positive electrode material precursor can be obtained; S40: take lithium metaborate and put it into a beaker, add 50 mL of deionized water and stir for 30 minutes, then immerse the manganese-based positive electrode material precursor in the above solution and stir at room temperature for 30 minutes;
[0046] S50: The beaker is moved into an oven and dried and evaporated at 80° C. to obtain a manganese-based positive electrode material, and a self-assembled protective layer is formed in the process.
[0047] The preparation method utilizes the product after the metaboric acid-based compound is dissolved in water to process the manganese-based positive electrode material, and forms a manganese-based compound and a metaboric acid-based compound composite positive electrode material in an aqueous solution. This process is simple and easy to operate, and will not affect the main structure of the manganese-based positive electrode material. The reversible boron-containing protective layer (including MnBx, zinc boride, etc., x is 1 / 2, 1, 2, etc.) formed during the charge and discharge process suppresses the excessive deposition of by-products, forms a solid positive electrode-electrolyte interface framework, suppresses the dissolution of manganese ions, and greatly improves the cycle stability of manganese-based positive electrode materials. The preparation method is simple in process, easy to control, and has good repeatability. It can realize large-scale application. The preparation method is not limited to the material disclosed in the present invention, and can also be used for the post-treatment of other zinc ion battery positive electrode materials. The method has a large application space and has a broad application prospect.
[0048] In one example of the present invention, in step S10, the strong oxidant is permanganate, persulfate or peroxide.
[0049] In one example of the present invention, the strong oxidant is AMnO4, wherein A is at least one of six metal ions of Li, Na, K, Ca, Mg, and Zn; the persulfate is MS2O8, wherein M is at least one of three substances of NH4, Na, and K; and the peroxide is at least one of two substances of K2O2 and H2O2.
[0050] In one example of the present invention, in step S10, the manganese salt is at least one of manganese sulfate, manganese acetate, manganese chloride, and manganese carbonate.
[0051] In one example of the present invention, in the step S30, after cooling, precipitation, filtration, washing for multiple times, the precursor is placed in an oven at 80-110° C. and vacuum dried to obtain a manganese-based positive electrode material precursor.
[0052] In one example of the present invention, in step S40, the metaboric acid-based compound is RBO2, wherein R is at least one of seven substances: Li, Na, K, Fe, Mg, Mn, and Al.
[0053] In one example of the present invention, in step S40, the mass ratio of the manganese-based oxide to the metaboric acid-based compound is 1:0.01-0.5.
[0054] In one example of the present invention, in step S40, the beaker is moved into an oven at 60-80°C for drying and evaporation to obtain a manganese-based positive electrode material, and a manganese-based compound and a metaboric acid-based compound composite positive electrode material are formed in the process. .
[0055] Another object of the present invention is to propose an application of the method for preparing a manganese-based positive electrode material for a zinc ion battery as described above to prepare a positive electrode material, and the positive electrode material prepared by the preparation method is applied to the positive electrode material of a zinc ion battery or a power battery.
[0056] That is to say, the manganese-based positive electrode material for zinc ion batteries with added metaboric acid-based compounds is used as a positive electrode material in the field of zinc ion batteries or power batteries.
[0057] Specific examples
[0058] Example 1: Post-treatment of δ-MnO2 cathode material using lithium metaborate
[0059] The original manganese-based positive electrode material was directly synthesized by a one-step hydrothermal method. 12mmol potassium permanganate and 2mmol manganese sulfate were placed in a beaker under mechanical stirring, and 60mL deionized water was added and stirred for 1 hour. After that, the above solution was transferred into a high-pressure reactor (100mL) with a polytetrafluoroethylene liner, and then placed in an oven heated to 160°C for 12 hours. After cooling, the original sample of the manganese-based positive electrode material was obtained, and then further precipitated, filtered and washed with deionized water for several times, and then placed in an oven at 110°C for vacuum drying. The manganese-based positive electrode material with added lithium metaborate was obtained by a simple solution method. 0.02g of lithium metaborate was placed in a beaker, 50mL of deionized water was added and stirred for 30min, and then 0.5g of the original manganese-based positive electrode material powder was immersed in the above solution and stirred at room temperature for 30min. Finally, the beaker was moved into an oven and dried and evaporated at 80°C to obtain a manganese-based positive electrode material with added lithium metaborate. Figure 1 The transmission electron microscope images of the samples before and after treatment show that δ-MnO2@lithium metaborate composite cathode material is formed. Figure 2 This is the X-ray diffraction pattern of the sample powder before and after treatment. The structure and composition of the positive electrode material can be seen from the figure. Figure 3These are the XPS images of the samples before and after treatment. It can be seen that the crystal structure of the sample has not changed after treatment. Figure 4 The XRD images of the treated samples during the charge and discharge process show that the treated samples formed a reversible boron-containing protective layer (including MnBx, zinc boride, etc., x is 1 / 2, 1, 2, etc.) during the charge and discharge process. Button cells were used for electrochemical performance testing. The sample, conductive carbon black and binder (polyvinylidene fluoride) were mixed in a mass ratio of 7:2:1, and an appropriate amount of solvent NMP (N-methylpyrrolidone) was added. After being mixed into a slurry, it was evenly coated on a titanium foil and vacuum dried at 110°C to obtain a pole piece. A metal zinc sheet was used as the counter electrode, and 2 mol·L -1 ZnSO4 and 0.1 mol·L -1 MnSO4 was used as electrolyte, glass fiber filter paper was used as separator (GF-D), and the loading of active materials was about 0.8-1.5 mg cm -2 , assembled into 2032 button cells in an air environment. Using NEWARE TC53 battery test system, charge and discharge tests were performed at a constant current density, with a charge and discharge voltage range of 0.8 to 1.8 V, and charge and discharge current densities of 500, 1000, 2000, and 4000 mA / g, respectively. Figure 4 The cycle characteristic curve obtained for the test shows that the capacity of the positive electrode material before material treatment after cycling at different current densities is 81.8mAh / g, 84.2mAh / g, 41.1mAh / g, and 25.4mAh / g, respectively. The capacity of the positive electrode material after treatment after cycling at different current densities is 229.5mAh / g, 210.5mAh / g, 101.2mAh / g, and 95.2mAh / g, respectively. The δ-MnO2 positive electrode material for zinc ion batteries with the addition of lithium metaborate exhibits excellent cycle performance and rate performance.
[0060] Example 2: Post-treatment of α-MnO2 cathode material using sodium metaborate
[0061] The original manganese-based positive electrode material was directly synthesized by a one-step hydrothermal method. 1 ml of 38 wt% concentrated hydrochloric acid was added to 45 ml of 2.5 mmol potassium permanganate aqueous solution under mechanical stirring and stirred for 30 minutes. After that, the above solution was transferred into a high-pressure reactor (100 mL) with a polytetrafluoroethylene liner, and placed in an oven preheated to 140 ° C for 12 hours. After cooling, the original sample of the manganese-based positive electrode material was obtained, and then further precipitated, filtered and washed with deionized water for several times, and then placed in an oven at 80 ° C for vacuum drying. The manganese-based positive electrode material with added sodium metaborate was obtained by a simple solution method. Take 0.02 g of sodium metaborate and put it into a beaker, add 50 mL of deionized water and stir for 30 minutes, then immerse 0.5 g of the original manganese-based positive electrode material powder in the above solution and stir at room temperature for 30 minutes. Finally, the beaker was moved into an oven and dried and evaporated at 80 ° C to obtain the manganese-based positive electrode material with added sodium metaborate. The transmission electron microscopy results of the samples before and after treatment showed that the samples after adding sodium metaborate formed α-MnO2@sodium metaborate composite positive electrode materials. The X-ray diffraction spectrum results of the sample powders before and after treatment showed that the structure and composition of the positive electrode materials did not change before and after treatment. The XPS results of the samples before and after treatment showed that there was a certain boron compound on the surface of the treated samples. The XRD images of the treated samples during the charge and discharge process showed that the treated samples formed a reversible boron-containing protective layer (including MnBx, zinc boride, etc., x is 1 / 2, 1, 2, etc.). The electrochemical performance test was carried out using a button cell. The sample, conductive carbon black and binder (polyvinylidene fluoride) were mixed in a mass ratio of 7:2:1, and an appropriate amount of solvent NMP (N-methylpyrrolidone) was added. After being mixed into a slurry, it was evenly coated on a titanium foil and vacuum dried at 110°C to obtain a pole piece. A metal zinc sheet was used as the counter electrode, and 2 mol·L -1 ZnSO4 and 0.1 mol·L -1 MnSO4 was used as electrolyte, glass fiber filter paper was used as separator (GF-D), and the loading of active materials was about 0.8-1.5 mg cm -2, assembled into 2032 button cells in an air environment. Using NEWARE TC53 battery test system, charge and discharge tests were carried out at a constant current density, the charge and discharge voltage range was 0.8-1.8V, and the charge and discharge current densities were selected as 500, 1000, 2000, and 4000mA / g. At charge and discharge currents of 500, 1000, 2000, and 4000mA / g, the capacities of the untreated positive electrode materials after charge and discharge (500mA / g cycle 200 times, 1000mA / g cycle 300 times, 2000mA / g cycle 800 times, 4000mA / g cycle 1000 times) were 135.2mAh / g, 112.4mAh / g, 88.5mAh / g, and 74.8mAh / g, respectively. The capacities of the treated positive electrode materials after cycling at different current densities were 239.8 mAh / g, 212.6 mAh / g, 124.5 mAh / g, and 91.2 mAh / g, respectively. The α-MnO2 positive electrode material for zinc ion batteries with sodium metaborate added showed excellent cycling performance and rate performance.
[0062] Example 3: Post-treatment of β-MnO2 cathode material using potassium metaborate
[0063] The original manganese-based cathode material was directly synthesized by a one-step hydrothermal method. 4mmol potassium persulfate and 4mmol manganese sulfate were placed in a beaker under mechanical stirring, and 70mL deionized water was added and stirred for 2 hours. After that, the above solution was transferred into a high-pressure reactor (100mL) with a polytetrafluoroethylene liner, and then placed in an oven heated to 140°C for 12 hours. After cooling, the original sample of the manganese-based cathode material was obtained, and then further precipitated, filtered and washed with deionized water for several times, and then placed in a 70°C oven for vacuum drying. The manganese-based cathode material with potassium metaborate added was obtained by a simple solution method. Take 0.02g of potassium metaborate and put it into a beaker, add 50mL of deionized water and stir for 30min, then immerse 0.5g of the original manganese-based cathode material powder in the above solution and stir at room temperature for 30min. Finally, the beaker was moved into an oven and dried and evaporated at 80°C to obtain a manganese-based cathode material with potassium metaborate added. The transmission electron microscopy results of the samples before and after treatment showed that the samples after adding potassium metaborate formed β-MnO2@potassium metaborate composite positive electrode materials. The X-ray diffraction spectrum results of the sample powders before and after treatment showed that the structure and composition of the positive electrode materials did not change before and after treatment. The XPS results of the samples before and after treatment showed that there was a certain boron compound on the surface of the treated samples. The XRD images of the treated samples during the charge and discharge process showed that the treated samples formed a reversible boron-containing protective layer (including MnBx, zinc boride, etc., x is 1 / 2, 1, 2, etc.). The electrochemical performance test was carried out using a button cell. The sample, conductive carbon black and binder (polyvinylidene fluoride) were mixed in a mass ratio of 7:2:1, and an appropriate amount of solvent NMP (N-methylpyrrolidone) was added. After being mixed into a slurry, it was evenly coated on a titanium foil and vacuum dried at 110°C to obtain a pole piece. A metal zinc sheet was used as the counter electrode, and 2 mol·L -1 ZnSO4 and 0.1 mol·L -1 MnSO4 was used as electrolyte, glass fiber filter paper was used as separator (GF-D), and the loading of active materials was about 0.8-1.5 mg cm -2, assembled into 2032 button cells in an air environment. Using NEWARE TC53 battery test system, charge and discharge tests were carried out at a constant current density, the charge and discharge voltage range was 0.8-1.8V, and the charge and discharge current densities were selected as 500, 1000, 2000 and 4000mA / g respectively. At the charge and discharge currents of 500, 1000, 2000, and 4000mA / g, the capacities of the untreated positive electrode materials after charge and discharge (500mA / g cycle 200 times, 1000mA / g cycle 300 times, 2000mA / g cycle 800 times, 4000mA / g cycle 1000 times) were 121.2mAh / g, 100.4mAh / g, 75.5mAh / g, and 62.8mAh / g respectively. The capacities of the treated cathode materials after cycling at different current densities were 219.8 mAh / g, 202.3 mAh / g, 114.5 mAh / g, and 81.7 mAh / g, respectively. The β-MnO2 cathode material for zinc ion batteries with potassium metaborate showed excellent cycling performance and rate performance.
[0064] Example 4: Post-treatment of λ-MnO2 cathode material using lithium metaborate
[0065] The original manganese-based positive electrode material was synthesized by a one-step hydrothermal method and calcination. 2.5g potassium permanganate and 1.5g manganese acetate were placed in a beaker under mechanical stirring, and 80mL deionized water was added and stirred for 30 minutes. After that, the above solution was transferred into a high-pressure reactor (100mL) with a polytetrafluoroethylene liner, and then placed in an oven heated to 160°C for 12 hours. After cooling, it was precipitated, filtered and washed with deionized water for many times, placed in an oven at 80°C for vacuum drying, and then placed in an oven at 450 degrees Celsius for calcination for 4h to obtain the original sample of manganese-based positive electrode material. The manganese-based positive electrode material with added lithium metaborate was obtained by a simple solution method. 0.02g lithium metaborate was placed in a beaker, 50mL deionized water was added and stirred for 30min, and then 0.5g of the original manganese-based positive electrode material powder was immersed in the above solution and stirred at room temperature for 30min. Finally, the beaker was moved into an oven and dried and evaporated at 80°C to obtain a manganese-based positive electrode material with lithium metaborate added. The transmission electron microscopy results of the samples before and after treatment showed that the samples after adding lithium metaborate formed a λ-MnO2@lithium metaborate compound composite positive electrode material. The X-ray diffraction spectrum of the sample powders before and after treatment showed that the structure and composition of the positive electrode material did not change before and after treatment. The XPS results of the samples before and after treatment showed that a certain boron compound existed on the surface of the treated samples. The XRD images of the treated samples during the charge and discharge process showed that the treated samples formed a reversible boron-containing protective layer (including MnBx, zinc boride, etc., x is 1 / 2, 1, 2, etc.). The electrochemical performance test was carried out using a button cell. The sample, conductive carbon black and binder (polyvinylidene fluoride) were mixed in a mass ratio of 7:2:1, and an appropriate amount of solvent NMP (N-methylpyrrolidone) was added. After being mixed into a slurry, it was evenly coated on a titanium foil and vacuum dried at 110°C to obtain a pole piece. Using zinc sheet as counter electrode, 2 mol·L -1 ZnSO4 and 0.1 mol·L -1 MnSO4 was used as electrolyte, glass fiber filter paper was used as separator (GF-D), and the loading of active materials was about 0.8-1.5 mg cm -2, assembled into 2032 button cells in an air environment. Using NEWARE TC53 battery test system, charge and discharge tests were carried out at a constant current density, the charge and discharge voltage range was 0.8-1.8V, and the charge and discharge current densities were selected as 500, 1000, 2000, and 4000mA / g. At charge and discharge currents of 500, 1000, 2000, and 4000mA / g, the capacities of the untreated positive electrode materials after charge and discharge (500mA / g cycle 200 times, 1000mA / g cycle 300 times, 2000mA / g cycle 800 times, 4000mA / g cycle 1000 times) were 145.7mAh / g, 128.2mAh / g, 97.5mAh / g, and 87.5mAh / g, respectively. The capacities of the treated positive electrode materials after cycling at different current densities were 254.1 mAh / g, 227.2 mAh / g, 147.5 mAh / g, and 114.9 mAh / g, respectively. The λ-MnO2 positive electrode material for zinc ion batteries with lithium metaborate added exhibited excellent cycling performance and rate performance.
[0066] Example 5: Post-treatment of Mn3O4 cathode material using aluminum metaborate
[0067] The original manganese-based cathode material was directly synthesized by electrodeposition. Carbon cloth was used as the working electrode, 0.1M Mn(CH3COO)2 and 0.1M Na2S2O8 were used as the mixed electrolyte, and platinum foil was used as the counter electrode. Then, the electrodeposition was carried out at a constant potential of 1.8V for 20 minutes, and the loading capacity was about 1.5mgcm -2Mn3O4. Then, it was further precipitated, filtered and washed with deionized water for several times, and then placed in a 110°C oven for vacuum drying. A manganese-based positive electrode material with aluminum metaborate added was obtained by a simple solution method. 0.02g of aluminum metaborate was put into a beaker, 50mL of deionized water was added and stirred for 30min, then 0.5g of the original manganese-based positive electrode material powder was immersed in the above solution and stirred at room temperature for 30min. Finally, the beaker was moved into an oven and dried and evaporated at 80°C to obtain a manganese-based positive electrode material with aluminum metaborate added. The transmission electron microscopy results of the samples before and after treatment showed that the samples after adding aluminum metaborate formed a Mn3O4@aluminum metaborate composite positive electrode material. The X-ray diffraction spectrum of the sample powders before and after treatment showed that the structure and composition of the positive electrode materials did not change before and after treatment. The XPS results of the samples before and after treatment showed that a certain boron compound existed on the surface of the treated samples. The XRD images of the treated samples during the charge and discharge process show that the treated samples form a reversible boron-containing protective layer (including MnBx, zinc boride, etc., x is 1 / 2, 1, 2, etc.). The electrochemical performance test was carried out using button cells. The sample, conductive carbon black and binder (polyvinylidene fluoride) were mixed in a mass ratio of 7:2:1, and an appropriate amount of solvent NMP (N-methylpyrrolidone) was added. After mixing into a slurry, it was evenly coated on the titanium foil and vacuum dried at 110°C to obtain the electrode. The metal zinc sheet was used as the counter electrode, and 2 mol·L -1 ZnSO4 and 0.1 mol·L -1 MnSO4 was used as electrolyte, glass fiber filter paper was used as separator (GF-D), and the loading of active materials was about 0.8-1.5 mg cm -2 , assembled into 2032 button cells in an air environment. Using NEWARE TC53 battery test system, charge and discharge tests were carried out at a constant current density, the charge and discharge voltage range was 0.8-1.8V, and the charge and discharge current densities were 500, 1000, 2000, and 4000mA / g. At charge and discharge currents of 500, 1000, 2000, and 4000mA / g, the capacities of the untreated positive electrode materials after charge and discharge (500mA / g cycle 200 times, 1000mA / g cycle 300 times, 2000mA / g cycle 800 times, 4000mA / g cycle 1000 times) were 104.2mAh / g, 87.4mAh / g, 65.4mAh / g, and 45.7mAh / g, respectively. The capacities of the treated positive electrode materials after cycling at different current densities were 145.6 mAh / g, 124.4 mAh / g, 104.7 mAh / g, and 88.5 mAh / g, respectively. The Mn3O4 positive electrode material for zinc ion batteries with aluminum metaborate showed excellent cycling performance and rate performance.
[0068] The above describes in detail an exemplary implementation of a manganese-based positive electrode material for a zinc ion battery and a preparation method and application thereof proposed in the present invention with reference to preferred embodiments. However, those skilled in the art will appreciate that, without departing from the concept of the present invention, various modifications and variations may be made to the above specific embodiments, and various technical features and structures proposed in the present invention may be combined in various ways without exceeding the protection scope of the present invention, which is determined by the appended claims.
Claims
1. A manganese-based positive electrode material for a zinc ion battery, characterized in that: The positive electrode material is a composite material formed by adding a metaborate-based compound to a manganese-based oxide, wherein the metaborate-based compound includes at least one of lithium metaborate, sodium metaborate, potassium metaborate, iron metaborate, magnesium metaborate, manganese metaborate, and aluminum metaborate; the manganese-based oxide includes at least one of α-MnO2, β-MnO2, γ-MnO2, δ-MnO2, T-MnO2, λ-MnO2, Mn2O3, Mn3O4, and ZnMn2O4.
2. A method for preparing a manganese-based positive electrode material for a zinc ion battery as claimed in claim 1, characterized in that: The steps include: S10: Put the strong oxidant and manganese salt into a beaker under mechanical stirring, add deionized water and stir evenly; S20: transferring the above solution into a high pressure reactor with a polytetrafluoroethylene liner, and then heating it in an oven; S30: After cooling, precipitation, filtration, washing, and multiple times, the precursor of the manganese-based positive electrode material is obtained by vacuum drying in an oven; S40: Put a metaboric acid compound into a beaker, add deionized water and stir, immerse the manganese-based positive electrode material precursor in the solution, and stir at room temperature; S50: The beaker is moved into an oven for drying and evaporation to obtain a manganese-based positive electrode material. During the process, a manganese-based compound and a metaboric acid-based compound composite positive electrode material is formed.
3. The method for preparing a manganese-based positive electrode material for a zinc ion battery according to claim 2, wherein: In step S10, the strong oxidant is permanganate, persulfate or peroxide.
4. The method for preparing a manganese-based positive electrode material for a zinc ion battery according to claim 3, wherein: The strong oxidant is AMnO4, wherein A is at least one of six metal ions of Li, Na, K, Ca, Mg, and Zn; the persulfate is MS2O8, wherein M is at least one of three substances of NH4, Na, and K; and the peroxide is at least one of two substances of K2O2 and H2O2.
5. The method for preparing a manganese-based positive electrode material for a zinc ion battery according to claim 2, wherein: In step S10, the manganese salt is at least one of manganese sulfate, manganese acetate, manganese chloride and manganese carbonate.
6. The method for preparing a manganese-based positive electrode material for a zinc ion battery according to claim 2, characterized in that: In the step S30, after cooling, precipitation, filtration, washing for multiple times, the product is placed in an oven at 80-110° C. and vacuum dried to obtain a manganese-based positive electrode material precursor.
7. The method for preparing a manganese-based positive electrode material for a zinc ion battery according to claim 2, characterized in that: In step S40, the boric acid-based compound is RBO2, wherein R is at least one of seven substances: Li, Na, K, Fe, Mg, Mn, and Al.
8. The method for preparing a manganese-based positive electrode material for a zinc ion battery according to claim 2, characterized in that: In step S40, the mass ratio of the manganese-based oxide to the metaboric acid-based compound is 1:0.01-0.
5.
9. The method for preparing a manganese-based positive electrode material for a zinc ion battery according to claim 2, characterized in that: In the step S40, the beaker is moved into an oven at 60-80°C for drying and evaporation to obtain a manganese-based positive electrode material, during which a manganese-based compound and a metaboric acid-based compound composite positive electrode material is formed.
10. An application of the method for preparing a manganese-based positive electrode material for a zinc ion battery as claimed in any one of claims 2 to 9 to prepare a positive electrode material, characterized in that: The positive electrode material prepared by the preparation method is applied to the positive electrode material of zinc ion batteries or power batteries.
Citation Information
Patent Citations
Manganese dioxide asymmetric super capacitor and manufacturing method thereof
CN102683037A
Aqueous zinc-ion battery positive electrode material
CN107863485A
Preparation method of nanocomposite material for cathodes of aqueous zinc ion batteries
CN110190272A
Modified layered lithium-rich manganese oxide positive electrode material and application thereof
CN113991081A
Sea urchin-shaped manganese oxide positive electrode material for zinc ion battery and preparation method
CN118619350A